Modern physical metallurgy and materials engineering science, process, applications. - Smallman, R. E. (Butterworth Heinemann, 1999)
For many years, various editions of Smallman's Modern Physical Metallurgy have served throughout the world as a standard undergraduate textbook on metals and alloys. In 1995, it was rewritten and enlarged to encompass the related subject of materials science and engineering and appeared under the title Metals & Materials: Science, Processes, Applications offering a comprehensive amount of a much wider range of engineering materials. Coverage ranged from pure elements to superalloys, from glasses to engineering ceramics, and from everyday plastics to in situ composites, Amongst other favourable.